Are the Well-known Economic Hypotheses about the Effects of Inflation and Devaluation Suitable for Ukraine? - Vasylenko, Yuri V. (Ekonomika, 2015)
In Ukraine, the well-known position of the Keynesian theory of the utility of moderate inflation is not confirmed. There is no such a level of price increase which would cause the improvement of the economy. Any inflation reduces the real GDP.If inflation falls short of the devaluation, the real GDP index increases the more the more is the lag. If no lagging, the GDP decreases.Devaluation is not always beneficial for exporters and for the country on the whole as claimed by the traditional theory of foreign trade. If devaluation has been done, exporters must lobby curb domestic prices.Emission may give a positive result only if the government will manage to keep inflation.The most effective direction of emission is to invest in companies and to cover the budget deficit. Additional emissions as a support of banks destroys the economy at any inflation. The IMF, providing loans or help to Ukraine, should prohibit this action because it is one of the powerful ways of thefts.
Keywords: causal model; inflation; devaluation; emission; export